Elastic Anisotropy of 1, 3, 5‐Triamino‐2, 4, 6‐Trinitrobenzene as a Function of Temperature and Pressure: A Molecular Dynamics Study. Issue 8 (15th June 2022) - Lafourcade, Paul; Maillet, Jean‐Bernard; Bruzy, Nicolas; Denoual, Christophe
Abstract: The equation of state of the triclinic compound 1, 3, 5‐triamino‐2, 4, 6‐trinitrobenzene (TATB) as well as its second‐order isothermal elastic tensor were computed through classical molecular dynamics simulations under various temperature and pressure conditions. Hydrostatic pressures similar to previous diamond anvil cell experiments were imposed up to 60 GPa and temperatures chosen between 100 and 900 K in conjunction with the most recent version of an all‐atom fully flexible molecule force field. The isothermal elastic constants were computed using the generalized Hooke's law by fitting Cauchy stress vs. linear strain curves for pressures below 50 GPa. Along isobaric loadings, TATB single crystal stiffnesses are found to undergo softening, less pronounced at high pressure, while maintaining its elastic anisotropy. On the other hand, along an isothermal loading, a non‐linear increase is observed in the elastic constants with respect to pressure with a significant decrease in anisotropy. Towards a precise mesoscopic modelling of TATB single crystal mechanical behavior, we provide "ready to plug‐in" analytical formulations of the P, V, T equation of state and pressure‐temperature dependent non‐linear elasticity. Abstract :